Pengaruh Terapi Kompres Hangat pada Tempat Penyuntikan Terhadap Respon Nyeri pada Bayi Saat Imunisasi Campak di Desa Pedekok Kec. Pegasing Kab. Aceh Tengah Tahun 2022 - Aida Fitri; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Heni Tiurmaida (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Warm compress is a nursing action by providing warmth to a certain area using a bag filled with warm water so that it creates a warm feeling in the part of the body that needs it. Warm compress can relieve pain and improve the healing process. The purpose of this study was to analyze the effect of warm compress therapy at the injection site on pain in infants during measles immunization in Pedekok Village, Pegasing District, Central Aceh Regency in 2022. The method in this study is a Quasi Experimental research type with a research design using the Post test only control group design approach. This research was conducted in Pedekok Village, Pegasing District, Central Aceh Regency in 2022, the population in this study was 40 toddlers. then the sample is part of all the objects studied and is considered to represent the entire population. The number of samples used is 40 people using the Non-probability sampling technique. The data collection technique uses a questionnaire sheet and a respondent observation sheet. the results of data analysis with the Mann Whitney Test obtained a Symp.sig value of 0.000 <0.05 meaning Ho is rejected. So it can be concluded that there is a significant effect between warm compress therapy at the injection site during measles immunization on pain responses in infants in Pedekok Village, Pegasing District, Central Aceh Regency in 2022.